A Literatur Review “Strategi Manajemen Risiko Untuk Meningkatkan Keselamatan Pasien di Rumah Sakit” - Sri Utami, Rahmawati; Erma Santi, Dwi; Zakiyah, Ana (NHM PRESS, 2024)
Patient safety incidents, one of which is the unexpected event of patient injury, should not occur in hospitals, so risk management programs are very important to implement, but in the implementation of the care process, patient safety incidents still occur. Implementing effective risk management is an important strategy to identify, analyze, and mitigate risks that may compromise patient safety. The purpose of this study was to review risk management strategies used in hospitals to improve patient safety. The method used in this literature review utilizes a comprehensive strategy, such as searching for articles in research journal databases, searching through the internet, reviewing articles. The database search used includes database searches used including Science Direct getting 29,162 articles, Pubmed getting 527 articles, Google Scholar getting 9370 articles, and Scopus getting 10 articles. The keywords used in the article search were risk management and patient safety. After going through the identification, screening and eligibility stages, 10 articles were obtained that were suitable through analysis of objectives, suitability of topics, research methods used, sample size, research ethics, results of each article, and limitations that occurred. The results showed that implementing an incident reporting system, regular staff training, improving standard operating procedures (SOP) and implementing health information technology are important steps to reduce patient safety incidents. Integrated and sustainable risk management has been shown to improve the quality of care and provide better protection to patients. This study recommends that hospitals continue to strengthen their safety practices and increase collaboration in risk management.